Production of synbiotic fermented soymilk from vegetable soybea - Battistini, Carolina (2016)
Vegetable soybeans [Glycine Max (L.) Merril] are harvested while seeds are immature which have some advantages over mature soybean, such as sweeter flavor and less content of indigestible oligosaccharides, stachyose and raffinose. Considering those beneficial characteristics the aim of this work was to study the fermentation process of soymilk from vegetable soybean and evaluate the influence of prebiotics, inulin and fructooligosaccharide, on physical-chemical and microbiological properties of the fermented beverage. Soymilk was produced by soaking 50 g of freeze-dried vegetable soybeans cultivar BRS-232 in 455 g of water for 10 minutes. The mixture was heated at 85 °C and blended for 3 minutes. The slurry was stirred for 5 minutes, filtered and the soymilk supplemented with 4 g·ml-1 fructooligosaccharides (FOS) or inulin, or a mixture of both. Fermented soymilk without the addition of prebiotic was also prepared. The four formulations were produced in triplicate. Soymilks were inoculated with 0.02% of a freeze-dried ABT-4 culture, containing Lactobacillus acidophilus La-5, Bifidobacterium animalis susbsp. lactis Bb-12 and Streptococcus thermophilus, incubated at 37 °C until pH reached 4.8 and stored at 5 °C for 28 days. Prebiotics had no effect on time needed to reach pH of 4.8 in soymilk that was obtained in 3.2 ± 0.2 h. Lactic acid production was 15 % higher in fermented soymilk with inulin during storage. Viable cell numbers of B. animalis remained above 108 cfu/mL in the fermented soymilk during storage while L. acidophilus decreased by 1 log cfu/mL in the same period. The content of stachyose and raffinose decreased after fermentation by 28.5% and 39.5 % respectively. Soymilk made with vegetable soybeans has a great potential as a vehicle to deliver probiotics to consumers. The total count of probiotics was higher than 1010 cfu in a daily portion of 100 mL of the fermented beverage.